Study of the correlation between vitamin D level and liver function in children with infectious mononucleosis - Zhang Yufeng, He Yixiu, Zhao Shaojie, Pan Menglan, Chen Bingzhang, Zhu Yafei (Xin yixue, 2023)
Objective To investigate the correlation between the serum level of 25-hydroxyvitamin D （25（OH）D） and liver function in children with infectious mononucleosis （IM）. Methods Ninety children with acute IM were enrolled into the IM group， and 40 healthy children who underwent physical examination during the same period were allocated into the control group. Serum level of 25（OH）D was determined by electrochemiluminescence and the viral load of Epstein-Barr virus DNA （EBV-DNA） in plasma was determined by quantitative fluorescent RT-PCR. Clinical data and serum 25（OH） D levels were compared between two groups. The correlation between 25（OH）D level and atypical lymphocytes， liver function parameters and plasma EBV-DNA in children with IM was analyzed. Results Serum 25（OH）D level in the IM group was significantly lower， whereas the 25（OH）D inadequacy rate was significantly higher than those in the control group （both P < 0.05）. Serum 25（OH）D level was negatively correlated with atypical lymphocytes in the IM group （P < 0.05）. The levels of alanine aminotransferase （ALT）， aspartate aminotransferase （AST）， glutamyl transpeptidase （GGT）， and adenosine deaminase （ADA） in IM children with serum 25（OH）D inadequacy were higher than those in their counterparts with adequate serum 25（OH）D （all P < 0.05）. No significant differences were found in total bilirubin （TBIL）， direct bilirubin （DBIL） and plasma EBV-DNA load between the adequate and inadequate subgroups （all P > 0.05）. In the IM group， serum 25（OH）D level was negatively correlated with ALT， GGT， and ADA （all P < 0.05）， whereas positively correlated with CHE （P < 0.05） and had no correlation with AST， TBIL or DBIL （all P > 0.05）. Conclusions Serum vitamin D insufficiency occurs in children with IM. Vitamin D may be involved in the incidence and development of the course of IM， which is probably associated with liver function impairment.